Antecendents of youth's ads avoidance in Facebook - Fanggidae, Jappy P. (Institute of Computer Science (IOCS), 2024)
This study investigates the effects of disruptions, complexity, negative experience and relevance on advertising avoidance by the youth in Facebook. The relationships are mediated by attitude toward ads in Facebook. The data were collected from 154 undergraduate students in Kupang - Indonesia. The data gathered underwent structural equation model analysis, revealing a noteworthy mediation index. This suggests that the connection between the independent variables and advertising avoidance is influenced by one's attitude toward advertising. However, the results show that negative experience was not a predictor for advertising avoidance. The present study offers new insight regarding antecedents of ads avoidance in social media, in particular Facebook among the youth, one of the biggest age group users of Facebook in Indonesia